The Correlation of Open Learning, Collaboration, Learning Tools, and Creative Problem Solving by Graduate Students in Thailand - Nonthamand, Narin; Na-Songkhla, Jaitip (International Journal of Emerging Technologies in Learning (iJET), 2018)
Objectives of this research study were to investigate the correlation and forecast the independent variables of the correlation of opinions regarding open learning, collaboration, creative problem solving and usage level of teaching and learning media for graduate students in Thailand. It was a quantitative research study which used a questionnaire to collect data. The question items in the instrument were check listed and a rating scale was established which had been approved for validity by an expert. The samples consisted of 419 higher education students from 16 universities using correlation analysis and multiple regression analysis. Research Findings 1 determined: Open learning was positively related to team working and willingness to work with others, group discussion behaviors, usage of teaching and learning media, and creative problem solving abilities. The highest results included the correlation of group discussion and creative problem solving abilities at 609**. Finding 2 included: Applied statistics methods including coefficient correlation analysis and multiple regression analysis were used to analyze open learning, group behavior, usage of teaching and learning media, creative problem solving abilities and resulted with the forecast equation showing creative problem solving abilities = .524, open learning = +.111, team working = + .317 , duty to work with others = + .099, group discussion behavior = * + .371, usage level of teaching and learning media = +. 087